Hubungan Antara Sikap Tentang Pencegahan Kekambuhan Dengan Kepatuhan Menjalankan Diit Hipertensi Pada Lansia Di Posyandu Bagas Waras Pabelan Kartasura - , Murniati; , Abi Muchlisin, S.KM., M.Kep (2017)
Hypertension contributes nearly 9.4 million deaths from cardiovascular disease each year. Hypertension is estimated to affect more than one in three adults aged 25 years and over, or approximately one billion people worldwide. Elderly is one group that has a high risk of developing hypertension. Efforts to maintain blood pressure to avoid complications of hypertension is very important for the elderly. Hypertension diet is one of the measures to control blood pressure and avoid a recurrence of hypertension in the elderly. This study aimed to determine the relationship between attitudes recurrence prevention with compliance running diit hypertension in the elderly in Bagas Sane Pabelan Kartasura. This research is quantitative descriptive correlative method with cross sectional approach. The study population has the elderly who suffer from hypertension in Bagas Sane Pabelan Kartasura, while the study sample was 42 people who obtained using total sampling method. Data collection used questionnaires, while data analysis using Chi Square test. Conclusion of the study is the attitude of the recurrence prevention of hypertension in the elderly are mostly moderate (45%), adherence to the diet of hypertension in the elderly are mostly moderate (36%), and there is a relationship attitude recurrence prevention of hypertension on dietary compliance of hypertension in the elderly Posyandu elderly Bagas sane Pabelan Kartasura, where the better attitude then also getting better compliance ((2Obs= 8.449; p-value = 0.015).